The Culture of Familial Dialogue according to some variables A Field Study on Families in Jableh (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Dialogue culture is considered an urgent necessity in the shade of what the Arab communities witnessed in the last times concerning the spreading of chauvinism and the refusal of admitting others. Acquiring this culture starts from the family and through the dialogue among its members. This will enable those members, in the future, of making a dialogue with the other and having an openness in dealing with him/her. Therefore, this current research discusses the culture of familial dialogue. It also shows the relation of some variables because of the family members' having the skills of listening and speaking. Two questionnaires were designed to achieve the goals of the study. One of those questionnaires was directed to the children and the other one was directed to the parents. Moreover, those questionnaires were applied on a sample of some families living in a residential quarter in Jableh known as Western Jbeibat. The number of the families involved in the study was 384. One of the most important results, which were found, was the weak positive relation between the level of education of the parents with the family members' having the skills of listening and speaking. This relation is of a statistical indication. These results also signified the existence of aweak positive relation, which was of a statistical indication, between the economic level of the family and the members' having the above-mentioned skills.